Fast and Memory-Efficient Neural Code Completion - Svyatkovskiy, Alexey; Lee, Sebastian; Hadjitofi, Anna; Riechert, Maik; Vicente Franco, Juliana; Allamanis, Miltos (Mining Software Repositories, 2020)
Code completion is one of the most widely used features of modern integrated development environments (IDEs). Deep learning has recently made significant progress in the statistical prediction of source code. However, state-of-the-art neural network models consume prohibitively large amounts of memory, causing computational burden to the development environment, especially when deployed in lightweight client devices. In this work, we reframe neural code completion from a generation task to a task of learning to rank the valid completion suggestions computed from static analyses. By doing so, we are able to design and test a variety of deep neural network model configurations. One of our best models consumes 6 MB of RAM, computes a single suggestion in 8 ms, and achieves 90% recall in its top five suggestions. Our models outperform standard language modeling code completion techniques in terms of predictive performance, computational speed, and memory efficiency. Furthermore, they learn about code semantics from the natural language aspects of the code (e.g. identifier names) and can generalize better to previously unseen code.